Arm Strength With The Forehand Ability Forehand Athlete Club Tennis Field Training (PTL) UNP - Suryanto, Masrudi; Atradinal, Atradinal; Apriyano, Berto (Yayasan Sekora, 2019)
This study aims to determine the relationship between arm muscle strength endurance (X) and the forehand ability of the UNP Field Tennis Training Club (PTL) athletes (Y) as the dependent variable. This research was conducted on 21 athletes of the UNP Field Tennis Association (PTL), consisting of 15 sons and 6 daughters. The sampling technique used purposive sampling, namely obtained only 15 male athletes aged 12-18 years. The data were collected by measuring the endurance of the arm muscles with a pull-up test and for measuring the ability of forehand strokes in tennis using a forehand drive test. Data analysis and research hypothesis testing using the product moment correlation analysis technique with a significant level ? = 0.05. From the data analysis, it was found that